The family-school-primary care triangle and the access to mental health care among migrant and ethnic minorities - Gonçalves, M. (2015)
Understanding the concepts of mental health and help seeking behaviours of migrant and ethnic minority families constitutes an important step toward improving the intercultural competence of health and education professionals. This paper addresses these goals among ethnic and migrant minorities in Portugal. For this a multi-informant approach was selected. The study involved nine focus groups (N = 39) conducted with different samples: young immigrants (12-17 years), immigrant parents, teachers and health professionals. The results showed similarities and differences in concepts of mental health, as well as help seeking processes. Stigma continued to be recognized as a barrier in the access to mental health care. The paper argues that providing adequate training on mental health on cultural diversity competencies to health and education professionals can contribute to a better inter-communication and -relation system in the family-school-primary care triangle and thus facilitate access to mental health care for youth